Sadie [compact disc, unabridged] - Summers, Courtney (Macmillan Audio, 2018)
Told from the alternating perspectives of nineteen-year-old Sadie who runs away from her isolated small Colorado town to find her younger sister's killer, and a true crime podcast exploring Sadie's disappearance.